Computer and Centrifuge Modeling of Decoupled Explosions in Civilian Tunnels - Dale S. Preece; Joe R. Weatherby; Thomas K. Blanchat; Neil T. Davie; James J. Calderone; Thomas C. Togami; Robert A. Benham (International Society of Explosives Engineers, 1998)
"Geotechnical structures ,such as underground bunkers, tunnels, and building foundations aresubjected to stress fields produced by..the gravity load on the structure and/or any overlyingstrata. These stress fields may be.. reproduced on a scaled model of the structure byproportionally increasing the gravity field through the use of a centrifuge. This technology canthen be used to assess the vulnerability of various geotechnical structures to explosive loading.Applications of this technology include assessing the effectiveness of earth penetrating weapons,evaluating the vulnerability of various structures, counter-terrorism, and model validation. Thisdocument describes the development of expertise in scale model explosive testing ongeotechnical structures using Sandia’s large scale centrifuge facility. This study focused onburied structures such as hardened storage bunkers or tunnels. Data from this study was used toevaluate the predictive capabilities oft existing hydrocodes and structural dynamics codesdeveloped at Sandia National Laboratories (such as Pronto/SPH, Pronto/CTH, and ALEGRA)."